Impact of positive surgical margin on biochemical recurrence in localized prostate cancer - Wonchul Lee; Bumjin Lim; Yoon Soo Kyung; Choung-Soo Kim (Prostate International, 2021)
Background: We analyzed the relationship between biochemical recurrence (BCR) and the status of positive surgical margin (PSM) in patients with pT3a prostate cancer (PCa). Materials and methods: Patients (n = 150) who underwent radical prostatectomy for pT3a PCa without nodal/distant metastasis were retrospectively reviewed between 2010 and 2013. The data regarding the status of PSM including the number, length, and margin Gleason score were collected. The predictors of BCR were analyzed using Cox regression hazard models. BCR-free survival was compared between the patients with negative surgical margin (NSM) and with PSM using Kaplan–Meier curves and log-rank tests. Results: PSM was noted in 74 patients (49.3%). Seventy-six patients (50.7%) had NSM and 38 patients (25.3%) had single PSM. Twenty patients (13.3%) had two PSMs and 16 patients (10.7%) had ≥3 PSMs. In total patients, the multivariate analysis demonstrated that a pathological Gleason score of ≥8 was significantly associated with BCR [hazard ratio (HR), 2.173; 95% confidence interval (CI), 1.244–3.797; P = 0.038]. In patients with PSM, the number of PSM more than two was significantly associated with BCR (HR, 2.723; 95% CI, 1.256–5.902; P = 0.011). PSM length of ≥3 mm was also a significant predictive factor (HR, 1.024; 95% CI, 0.994–1.055, P = 0.042). Patients with the highest margin Gleason score of ≥4 had poorer BCR-free survival than those with that of 3/no surgical margin. Conclusions: Number (more than one), length (≥3 mm), and higher margin Gleason score (≥4) of PSM were significantly associated with an increased likelihood of BCR in patients with pT3a PCa.